Kebijaksanaan Kriminalisasi Dalam Perda Dalam Pelaksanaan Otonomi Daerah - teguh prasetyo (Jurnal Hukum IUS QUIA IUSTUM, 2005)
The formulation of criminalization policy is different among local regulation for each district. Some of the local regulations raise problems because criminal regulations are in contradiction the higher regulation. In addition, the sanctions imposed by the districtregulations are different. The problems raise because there is no definite guidelines, and because ofthe difference between one act and another. Therefore, itis necessary to find out the criminalization and synchronism pattern in the district regulation which involvesthe vertical and horizontal synchronism.